Recent Progress of Small-molecule Inhibitors of O-GlcNAcase for Alzheimer’s Disease - Sun, Sheng; Cao, JinFa; Ji, Shujie; Wang, Jian (Mini Reviews in Medicinal Chemistry, 2025)
O-GlcNAcylation is a non-canonical form of protein glycosylation that occurs in nuclear, cytoplasmic, and mitochondrial proteins among all multicellular eukaryotes. There are only two enzymes that regulate this post-translational modification, one of which is O-GlcNAcase, a glycoside hydrolase that catalyzes the hydrolytic cleavage of O-GlcNAc from protein substrates. Related studies have shown that the reduction of O-GlcNAc levels is closely related to Alzheimer's disease, which is maintained by reducing the aggregation of tau via inhibiting O-GlcNAcase. Various small-molecule O-GlcNAcase inhibitors with different chemical structures have been developed and used as chemical probes to explore the O-GlcNAc pathway. Although many reported inhibitors have shown that O-GlcNAcase activity has single-digit nmol IC50 values in binding assays, and molecules, such as LY-3372689, have entered phase II clinical studies, further exploration of novel O-GlcNAcase inhibitors with higher inhibitory activity and specificity is still worthy of attention. This article reviews the pathogenesis and therapeutic role of O-GlcNAcase in Alzheimer's disease, as well as the recent progress of O-GlcNAcase small molecule inhibitors, including sugar-derived or non-sugar scaffolds, and summarizes the clinical progress and potential prospects of O-GlcNAcase inhibitors.
Keywords: nonsugar inhibitors